Stochastic Differential Algebraic Equations of Index 2 - Thi The, Nguyen (Lobachevskii journal of mathematics, 2024)
This paper aims to develop an appropriate notion of index 2 for stochastic differential algebraic equations. We prove a theorem on the existence and uniqueness of the solution for this class and provide bounds for the moments of the solution.